The Association Between Handgrip Strength and Predialysis Serum Sodium Level in Patients With Chronic Kidney Disease Stage 5D - Markaki, Anastasia; Kyriazis, Periklis; Dermitzaki, Eleftheria-Kleio; Maragou, Sevasti; Psylinakis, Emmanuel; Spyridaki, Aspasia; Drosataki, Helen; Lygerou, Dimitra; Grammatikopoulou, Maria G.; Petrakis, Ioannis; Stylianou, Kostas (Frontiers in Medicine, 2021)
PURPOSE: Handgrip strength (HGS) is a useful tool for the systematic assessment of muscle function related to nutritional status. Reduced HGS has been associated with adverse clinical outcomes in chronic kidney disease (CKD) stage 5D patients. In the same patients, predialysis low serum sodium (sNa) has been associated with malnutrition and mortality. Here, we investigated the role of predialysis sNa on muscle function in CKD-5D patients. METHODS: We evaluated 45 patients on hemodialysis (HD) and 28 patients on peritoneal dialysis (PD) with HGS measurement, bioimpedance analysis, anthropometric measures, and malnutrition inflammation score (MIS). According to established diagnostic criteria, reduced HGS was defined as strength below 30Kg and 20Kg in men and women respectively. Predialysis sNa values were defined as the mean of all predialysis measurements during the preceding 6 months. Data analysis was performed separately for each of the HD and PD groups. RESULTS: The proportions of reduced HGS did not differ between the HD (66%) and PD (54%) groups, respectively. Patients in the HD group as compared to those in the PD group had higher serum albumin and potassium and mid-arm muscle circumference and lower residual renal function (RRF) and residual urine volume. Multivariate logistic analysis, after controlling for muscle mass, nutritional biomarkers, MIS, fluid overload and RRF, showed that for every 1mmol/l increase of sNa the odds of reduced HGS was decreased by 60% (OR= 0.40, 95% CI: 0.16-0.99) and 42% (OR= 0.58, 95% CI: 0.36-0.93) in HD and PD patients, respectively. However, stratified analysis indicated that lower sNa levels predicted reduced HGS in individuals with a background of malnutrition, inflammation, overhydration, and less preserved RRF, representing unfavorable conditions strongly related to muscle wasting in the dialysis setting. CONCLUSIONS: Predialysis sNa is a strong and independent determinant of HGS, a reliable nutritional marker in CKD-5D stage patients. However, according to our findings, lower sNa levels appear to be a marker of underlying unfavorable conditions that are heavily associated with reduced HGS, rather than a causal determinant of reduced HGS. Whether optimizing sNa levels improves patient muscle performance requires further investigations.